2015
DOI: 10.1016/j.toxlet.2015.07.013
|View full text |Cite
|
Sign up to set email alerts
|

Toxicity of Hexamoll® DINCH® following intravenous administration

Abstract: Alternative plasticizers to di(2-ethylhexyl) phthalate (DEHP) for blood bags have been sought for many years. Cyclohexane-1,2-dicarboxylic acid, diisononylester (Hexamoll(®) DINCH(®)) is an alternative that has been evaluated in preliminary studies for compatibility and efficacy to preserve whole blood. While Hexamoll(®) DINCH(®) has an extensive database for mammalian toxicity via oral administration, data were needed to evaluate toxicity from intravenous (IV) administration to support the use of the plastici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
26
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(29 citation statements)
references
References 18 publications
3
26
0
Order By: Relevance
“…Recent in vitro studies suggest that DINCH is a bioactive compound 29 , a potent metabolic disruptor 49 , and an endocrine disruptor 30 . The increase in hemorrhaging testes that we observed after DINCH exposure occurred at doses that were below or equal to the no observed adverse effect level (NOAEL) for parenteral exposure 50 . Together, these data suggest a need for a deeper exploration of the possible endocrine disruptive properties of DINCH.…”
Section: Discussionmentioning
confidence: 59%
“…Recent in vitro studies suggest that DINCH is a bioactive compound 29 , a potent metabolic disruptor 49 , and an endocrine disruptor 30 . The increase in hemorrhaging testes that we observed after DINCH exposure occurred at doses that were below or equal to the no observed adverse effect level (NOAEL) for parenteral exposure 50 . Together, these data suggest a need for a deeper exploration of the possible endocrine disruptive properties of DINCH.…”
Section: Discussionmentioning
confidence: 59%
“…Franken et al (2017) reported the high occurrence of asthma in Belgian teenagers (especially girls) associated with high DEHP and DnBP exposure 32 . DEHT and DINCH administration to rodents revealed no signs of DEHP-like toxicity [33][34][35] . However, DINCH in utero exposure has been associated with signs of impaired liver metabolism and premature testicular aging such as decreased testosterone secretion, physical changes in seminal glands and testicular atrophy in rats and their young offspring 36 .…”
Section: Introductionmentioning
confidence: 91%
“…In 2002, the plasticizer DINCH was introduced into the market, intended for the use in sensitive products such as toys, food contact materials and medical devices (Bhat et al, 2014;Biedermann-Brem et al, 2008;David et al, 2015;EFSA, 2006). DINCH is produced by catalytic hydrogenation of the aromatic ring of DINP, and commercialized as Hexamoll® DINCH® (Koch et al, 2013a).…”
Section: Introductionmentioning
confidence: 99%